Benzoylpyridine-based TADF emitters with AIE feature for efficient non-doped OLEDs by both evaporation and solution process. (May 2020) - Zhou, Xue; Xiang, Yepeng; Ni, Fan; Zou, Yang; Chen, Zhanxiang; Yin, Xiaojun; Xie, Guohua; Gong, Shaolong; Yang, Chuluo
Abstract: Fluorescent materials taking both advantages of evaporation and solution processes are urgently explored for the development of efficient and simplified organic light-emitting diodes (OLEDs). Furthermore, it is another huge challenge for such materials to achieve excellent electroluminescence performances in non-doped OLEDs. Herein, two new emitters, named as PyB-DPAC and PyB-DMAC with 4-benzoylpyridine moiety as the electron acceptor and 9, 9-diphenyl-9, 10-dihydroacridine or 9, 9-dimethyl-9, 10-dihydroacridine as the electron donor were synthesized and explored. Both emitters exhibit distinct TADF character, typical AIE feature and relatively high photoluminescence quantum yields. Accordingly, we demonstrated efficient non-doped vacuum-deposited OLED based on the PyB-DPAC with a maximum external quantum efficiency (EQE) up to 9.7%, and meanwhile an extremely low efficiency roll-off of 1.7% at a high brightness of 1000 cd m −2 . In addition, an impressive EQE of 11.1% can be realized from the solution-processed non-doped devices with the using of PyB-DPAC emitter. These affirmative results manifest that TADF emitters incorporate with the benzoylpyridine acceptor enabling a promising molecular design strategy in adapt to the non-doped evaporation- and solution-processed highly efficient OLEDs. Graphical abstract: Image 1 Highlights: Benzoylpyridine is used as acceptor to construct two new TADF emitters. Both emitters simultaneously exhibit distinct TADF character and typical AIE feature. The non-doped evaporation-/ solution-process devices based on PyB-DPAC exhibited maximum EQE of 9.7% / 11.1%, respectively. This work would be instructive in the rational molecular design of efficient non-doped solution-process emitters.